Multiple-source multiple-harmonic active vibration control of variable section cylindrical structures: A numerical study. (15th December 2016) - Liu, Jinxin; Chen, Xuefeng; Gao, Jiawei; Zhang, Xingwu
Abstract: Air vehicles, space vehicles and underwater vehicles, the cabins of which can be viewed as variable section cylindrical structures, have multiple rotational vibration sources (e.g., engines, propellers, compressors and motors), making the spectrum of noise multiple-harmonic. The suppression of such noise has been a focus of interests in the field of active vibration control (AVC). In this paper, a multiple-source multiple-harmonic (MSMH) active vibration suppression algorithm with feed-forward structure is proposed based on reference amplitude rectification and conjugate gradient method (CGM). An AVC simulation scheme called finite element model in-loop simulation (FEMILS) is also proposed for rapid algorithm verification. Numerical studies of AVC are conducted on a variable section cylindrical structure based on the proposed MSMH algorithm and FEMILS scheme. It can be seen from the numerical studies that: (1) the proposed MSMH algorithm can individually suppress each component of the multiple-harmonic noise with an unified and improved convergence rate; (2) the FEMILS scheme is convenient and straightforward for multiple-source simulations with an acceptable loop time. Moreover, the simulations have similar procedure to real-life control and can be easily extended to physical model platform. Highlights: Suppress periodic noise and perform real-system-resembled AVC simulation are demands. A stepped-up multiple-source multiple-harmonic AVC algorithm is proposed. An accelerated finite element model in-loop simulation (FEMILS) scheme is proposed. Numerical studies on a variable section cylindrical structure is conducted. Algorithm convergence is improved and FEMILS is verified to be valid and effective.